RETOLD: Review of the Meeting at the Universitat Autònoma de Barcelona (UAB), June 2022 - Clara Masriera i Esquerra (EXARC Journal)
In June 2022, the first onsite RETOLD project meeting took place in the Universitat Autònoma de Barcelona (UAB), hosted, and organised by the Prehistory department. This was the first time that all partners met face-to-face. The Prehistory department coordinates an MA in digital humanities as well as manages the archaeological research of different archaeological sites, some of which are actual archaeological open-air museums like “Campus d’Arqueologia de La Noguera” and “Campus d’Arqueologia de La Draga”, both in Catalonia.